Knee chondral delaminations and blisters - Mats Brittberg (Elsevier, 2022)
ABSTRACT: Cartilage injuries are well known to be troublesome and difficult to treat. Such injuries are partial and full thickness lesions most often easily detectable on MRI scanning. However, less well-known are lesions that start between the calcified bone (in the calcified zone) and the bone plate and they are called chondral delaminations. Such lesions often take time to detect. If not found and treated they may develop into full thickness lesions. In a short review, the diagnosis and treatment alternatives are discussed.